Evaluating privacy impact assessment methods: guidelines and best practice. (26th August 2019) - Vemou, Konstantina; Karyda, Maria
Abstract : Purpose: This paper aims to practically guide privacy impact assessment (PIA) implementation by proposing a PIA process incorporating best practices from existing PIA guidelines and privacy research. Design/methodology/approach: This paper critically reviews and assesses generic PIA methods proposed by related research, data protection authorities and standard's organizations, to identify best practices and practically support PIA practitioners. To address identified gaps, best practices from privacy literature are proposed. Findings: This paper proposes a PIA process based on best practices, as well as an evaluation framework for existing PIA guidelines, focusing on practical support to PIA practitioners. Practical implications: The proposed PIA process facilitates PIA practitioners in organizing and implementing PIA projects. This paper also provides an evaluation framework, comprising a comprehensive set of 17 criteria, for PIA practitioners to assess whether PIA methods/guidelines can adequately support requirements of their PIA projects (e.g. special legal framework and needs for PIA project organization guidance). Originality/value: This research extends PIA guidelines (e.g. ISO 29134) by providing comprehensive and practical guidance to PIA practitioners. The proposed PIA process is based on best practices identified from evaluation of nine commonly used PIA methods, enriched with guidelines from privacy literature, to accommodate gaps and support tasks that were found to be inadequately described or lacking practical guidance.